2023
DOI: 10.1111/hel.13006
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance, heteroresistance, and eradication success ofHelicobacter pyloriinfection in children

Abstract: BackgroundAntibiotic resistance is a well‐known factor of Helicobacter pylori eradication failure. Heteroresistance indicates the coexistence of resistant and susceptible strains and might lead to underestimating antimicrobial resistance. This study aims to evaluate the susceptibility profile, the frequency of heteroresistance of H. pylori strains, and their effect on eradication success in a pediatric population.Materials and MethodsChildren aged 2–17 years who underwent an upper gastrointestinal endoscopy fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Then, filter paper disks impregnated with standardized concentrations of a few different antibiotics are placed on the surface of predefined areas. The plates are incubated as described for the agar dilution method, and the size of the zone of inhibition around each of the disks is measured after 72 h [7,10]. However, this method has a labor-intensive nature stemming from manual measurements and data documentation, and mainly relies on investigator skill, leading to potential variations in results [38,39].…”
Section: • Disk Diffusion Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, filter paper disks impregnated with standardized concentrations of a few different antibiotics are placed on the surface of predefined areas. The plates are incubated as described for the agar dilution method, and the size of the zone of inhibition around each of the disks is measured after 72 h [7,10]. However, this method has a labor-intensive nature stemming from manual measurements and data documentation, and mainly relies on investigator skill, leading to potential variations in results [38,39].…”
Section: • Disk Diffusion Methodsmentioning
confidence: 99%
“…When compared to the agar dilution or broth dilution procedures, the E-test is straightforward to execute, and the results have been found to correlate closely with results obtained by the gold standard (agar dilution), except for metronidazole, for which recent studies have revealed inconsistency in the results [11]. The E-test possesses all the disadvantages that the disk diffusion method does [7,10,11].…”
Section: • E-testmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who underwent upper gastrointestinal endoscopy due to recurrent upper gastrointestinal symptoms of abdominal pain, acid reflux, vomiting or abdominal distention, and chronic gastritis, peptic ulcer or gastric cancer with family history, were included (Kotilea et al, 2023). Patients who received anti-H. pylori therapy within 4 weeks preceding the study, experienced subtotal gastrostomy, suffered from severe cardiovascular and respiratory diseases or recently consumed NSAID or alcohol, were excluded (Kotilea et al, 2023). In addition, all included patients did not brush their teeth or drink water in the morning.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The literature outlines numerous extra-digestive diseases potentially linked to HP infection, spanning neurological, dermatological, hematologic, ocular, cardiovascular, metabolic, and allergic conditions [ 15 , 16 , 17 , 18 ]. While some associations lack a clear explanation of the pathogenic mechanism, others exhibit a strong correlation, prompting guidelines for the treatment of HP infection to recommend determination and eradication therapy in these circumstances [ 19 ]. Overall, the implications of HP infection extend far beyond the digestive system, presenting a complex array of potential health consequences that continue to engage scientific inquiry and clinical attention.…”
Section: Introductionmentioning
confidence: 99%